Peran Kelompok Wanita Tani dalam Meningkatkan Ekonomi Keluarga di Kelurahan Tambakrejo Kecamatan Simokerto Kota Surabaya - Ramadhanty, Anjani Suci; Anshori, Moh. (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The assistance of the Women's Farming Group (KWT) in Tambakrejo Village, Simokerto District, Surabaya City aims to utilize the potential of vegetable crops such as mustard greens, kale, Brazilian spinach, pakchoy and lettuce so that they have economic value. Through the Forum Group Discussion (FGD), innovations were proposed in processing harvested produce into vegetable juice, which not only increases economic value but also family health. The main challenge faced is the low fluctuation in prices of fresh vegetables, so innovation in processing is needed. This assistance is expected to increase the capacity of KWT members, efficient resource management, and support from the government and non-governmental organizations. Women's involvement in KWT has the opportunity to increase their economic and social role, creating independence and solidarity among members. Further development steps include product diversification, ongoing training, provision of adequate infrastructure, and environmentally friendly waste management. With innovation and collaborative support, this program is expected to be able to empower women, improve family welfare, and strengthen the local economy in a sustainable manner, providing a positive impact on society.